Anti-inflammatory properties of the ethanol extract from Clerodendrum cyrtophyllum Turcz based on in vitro and in vivo studies. (23rd May 2020) - Nguyen, Thu Hang; Nachtergael, Amandine; Nguyen, Thi Mai; Cornet, Valérie; Duez, Pierre; Muller, Marc; Ly Huong, Duong Thi; Kestemont, Patrick
Abstract: Ethnopharmacological relevance: Clerodendrum cyrtophyllum Turcz, a plant belonging to the Verbenaceae family, has been used in traditional medicine for the treatment of various inflammatory diseases in many Asian countries. Aim of the study : The study aimed to evaluate anti-inflammatory properties of the ethanol extract from Clerodendrum cyrthophyllum Turcz leaves (EE-CC) through in vitro and in vivo models. Material and methods: Total phenolic and flavonoid contents in the extract were determined using colorimetric methods and HPTLC. In red blood cell membrane stabilization model, rat erythrocyte suspension was treated with crude ethanol extract at different concentrations, the hemoglobin content of the supernatant solution released by red blood hemolysis was estimated. We also evaluated the effects of the ethanol extract from this plant on the production of nitric oxide (NO), tumor necrosis factor alpha (TNF-α) in stimulated RAW 264.7 cells. In order to elucidate its anti-inflammatory molecular mechanisms, we further evaluated the effects of the EE-CC on the expression of the inflammatory genes in inflammation-induced zebrafish model by tail-cutting using qPCR analysis. Results: Colorimetric methods and HPTLC revealed high phenolic and flavonoid contents in the extract. In the red blood cell membrane stabilization model, the amount of hemoglobin released by red blood hemolysis significantly decreased in the presence of EE-CC, demonstrating a strong membrane stabilizing activity. EE-CC did not cause any toxic effect on cell viability but strongly inhibited NO and TNF-ɑ release due to LPS induction. The association with EE-CC significantly reduced the expression of cox-2, pla2, c3a, il-1(il1fma ), il-8 ( cxcl8b.1 ), tnf-α, and nf-ƙb, while increased the expression of the anti-inflammatory cytokine il-10 gene in cut-tail induced inflammation of zebrafish model. Conclusions: Taken together, the results suggest that the raw ethanol extract from C . cyrtophyllum Turcz leaves presents potent anti-inflammatory activities and may be useful for the treatment of various inflammatory diseases. Graphical abstract: Image 1